DETERMINATION OF THE MAGNETITE-WATER EQUILIBRIUM OXYGEN ISOTOPE FRACTIONATION FACTOR AT 350°C: A COMPARISON OF ION MICROPROBE AND LASER FLUORINATION TECHNIQUES - Fortier S.M.; Cole D.R.; Wesolowski D.J.; Riciputi L.R.; Paterson B.A.; Valley J.W.; Horita J. (My University, 1995)
A Cameca 4f ion microprobe has been used in conjunction with laser and conventional analytical techniques to measure the oxygen isotope fractionation between magnetite and water at 350°C. A set of experiments in which large (10-200 μm) magnetite crystals were grown from fine grained (0.2-2 μm) hematite starting material using four different isotopically labelled waters yields a value of 1000 ln α(mt-w) = -8.47 +/- 0.23, as determined by bulk oxygen extraction using laser fluorination. The value from the ion microprobe determination based on replicate analysis of magnetite single crystals is -8.60 +/- 0.65. The bulk analysis of one of the set of four experiments was used as an internal ion microprobe standard. The good agreement between the two techniques suggests that ion microprobe analyses may permit determination of isotope fractionation factors in experiments involving only a few percent of overall exchange.